Construction of a composite Hospital Admission Index using the aggregated weights of criteria - Nor Hasliza Mat Desa; Abdul Aziz Jemain; Maznah Mat Kasim (Universiti Kebangsaan Malaysia, 2015)
The issue of age difference in hospital admission should be given special attention since it affects the structure of hospital care and treatments. Patients of different age groups should be given different priority in service provision. Due to crucial time and limited resources, healthcare managers need to make wise decisions in identifying priorities in age of admission. This paper aimed to propose a construction of a daily composite hospital admission index (CHAI) as an indicator that captures relevant information about the overall performance of hospital admission over time. It involves five different age groups of total patients admitted to seven major public hospitals in the Klang Valley, Malaysia for respiratory and cardiovascular diseases for a period of three years, 2008 - 2010. The criteria weights were predetermined by aggregating the subjective weight based on rank ordered centroid (ROC) method and objective weight based on entropy - kernel method. The highest and lowest scores of CHAI were marked, while the groups of patients were prioritized according to the criteria weight ranking orders.